Synden – dogmatisk forstått - Christoffersen, Svein Aage (Dansk Teologisk Tidsskrift, 2008)
In her doctoral dissertation Kirsten Busch Nielsen argues that the understanding of sin in the works of Dietrich Bonhoeffer is based on the idea that the power of sin is broken in Jesus Christ. This idea is explored by a differentiated understanding of sin as transgression, as limitation and as limited in Christ. Through her thorough and thought provoking study of Bonhoeffer’s concept of sin Busch Nielsen makes a significant contribution not just to Bonhoeffer-research, but also to theological dogmatics. The study is however primarily focused on the early and late writings of Bonhoeffer, and for this reason important aspects of Bonhoeffer’s works in the 1930s are neglected. One misses above all a discussion of how Bonhoeffer’s biblical interpretations relates to his understanding of the concept of dogmatics. Her separation of dogmatics and ethics may also be questioned, not least from the point of view of Bonhoeffer himself. According to Busch Nielsen, Bonhoeffers moved significantly towards Karl Barth in his late works, but important traces of a more Lutheran understanding of simul iustus et peccator and Luther’s understanding of subiectum theologiae are overlooked.